2017
DOI: 10.1088/1367-2630/aa6c03
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit coupling in a hexagonal ring of pendula

Abstract: We consider the mechanical motion of a system of six macroscopic pendula which are connected with springs and arranged in a hexagonal geometry. When the springs are pre-tensioned, the coupling between neighbouring pendula along the longitudinal (L) and the transverse (T) directions are different: identifying the motion along the L and T directions as the two components of a spin-like degree of freedom, we theoretically and experimentally verify that the pre-tensioned springs result in a tunable spin-orbit coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…In these systems a spin-orbit coupling can be engineered by encoding an effective spin in two acoustic modes brought close to degeneracy. The experimental systems studied so far consist in discrete lattices of simple elementary mechanical systems, such as pendula [191,469] or gyroscopes [192], as well as acoustic crystals, made of a continuous fluid flowing in an engineered lattice geometry [206,470,471,472,473].…”
Section: Spin-orbit Coupling In Mechanical Systemsmentioning
confidence: 99%
“…In these systems a spin-orbit coupling can be engineered by encoding an effective spin in two acoustic modes brought close to degeneracy. The experimental systems studied so far consist in discrete lattices of simple elementary mechanical systems, such as pendula [191,469] or gyroscopes [192], as well as acoustic crystals, made of a continuous fluid flowing in an engineered lattice geometry [206,470,471,472,473].…”
Section: Spin-orbit Coupling In Mechanical Systemsmentioning
confidence: 99%
“…In order to keep the T symmetry intact, two opposite counter-propagating spins have to coexist at the same frequency according to Kramers degeneracy theorem. Hence, helical edge states have been detected in pendula lattices111,112 and predicted for Lamb and flexural waves in structured plates113,114 and granular crystals 115 .As detailed above, in addition to the pseudo spin, sound waves are capable of emulating a valley degree of freedom. Rather than pursuing novel carriers of information and energy similar to their electronic counterpart, recent efforts in the literature have demonstrated that valley Hall polarized mechanical states can give rise to topological protected vibrations.…”
mentioning
confidence: 93%
“…The asymptotic analysis shows that these nonlinear edge solitons are governed by the classical 1D NLS equation and are topologically protected in the same way as linear edge waves. The derivation can be readily generalized to other mechanical TIs with discrete elements [17,52], possibly with dissipation [53] and forcing [30] included. Further extensions may include TIs in continuous media that can exhibit significant nonlinearity, such as recent proposals based on magnetic solitons [54] and water waves [55].…”
mentioning
confidence: 99%